Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.ijrobp.2010.05.065
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Provider-Assessed and Patient-Reported Outcome Measures of Acute Skin Toxicity During a Phase III Trial of Mometasone Cream Versus Placebo During Breast Radiotherapy: The North Central Cancer Treatment Group (N06C4)

Abstract: Purpose Considerable interobserver variability exists among providers and between providers and patients when measuring subjective symptoms. In the recently published Phase III N06C4 trial of mometasone cream vs. placebo to prevent radiation dermatitis, the primary provider–assessed (PA) endpoint, using the Common Toxicity Criteria for Adverse Events (CTCAE), was negative. However, prospectively planned secondary analyses of patient-reported outcomes (PROs), using the Skindex-16 and Skin Toxicity Assessment To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 23 publications
(31 reference statements)
2
51
0
1
Order By: Relevance
“…This included disease specific modules of the European Organization for Research and Treatment of Cancer (EORTC) [1220] and Functional Assessment of Cancer Therapy (FACT) [2123] instruments, as well as the dermatology-specific Skindex-16, [24, 25] the EuroQol EQ-5D, [26] the Short-Form 36 Health Survey (SF-36) [27], and two recently developed bowel symptom inventories [28, 29]. Patient-adapted versions of the CTCAE were used in four studies [27, 3032], with visual analog scales used to capture patient-rated AEs in three studies [11, 33, 34].…”
Section: Resultsmentioning
confidence: 99%
“…This included disease specific modules of the European Organization for Research and Treatment of Cancer (EORTC) [1220] and Functional Assessment of Cancer Therapy (FACT) [2123] instruments, as well as the dermatology-specific Skindex-16, [24, 25] the EuroQol EQ-5D, [26] the Short-Form 36 Health Survey (SF-36) [27], and two recently developed bowel symptom inventories [28, 29]. Patient-adapted versions of the CTCAE were used in four studies [27, 3032], with visual analog scales used to capture patient-rated AEs in three studies [11, 33, 34].…”
Section: Resultsmentioning
confidence: 99%
“…Over the past few years, patient-reported outcomes have become common instruments to aid in accurate assessment of various symptoms (Neben-Wittich et al ., 2010). Recently, Neben-Wittich et al reported that the Skindex-16 and Skin Toxicity Assessment Tool, two patient-report outcomes (PRO) instruments, did not correlate with CTCAE scoring system.…”
Section: Areas Needing Investigation: Weaknesses In Measurement and Tmentioning
confidence: 99%
“…The study showed that African-Americans reported more severe post-treatment skin reactions compared to Caucasians after receiving radiation therapy. Both of these studies (Neben-Wittich et al ., 2010; Ryan et al ., 2007) demonstrate that patient-reported information is critical for effective symptom management. Overall, further research is required for development of a standard and accurate scoring system for radiation skin injury.…”
Section: Areas Needing Investigation: Weaknesses In Measurement and Tmentioning
confidence: 99%
“…Unfortunately, the measures used in this trial (Skindex, SF-36) did not evaluate pain [20]. Neben-Wittich et al compared the Skindex-16, STAT, and NIH CTC-AE in a phase III clinical trial testing mometasone cream versus placebo for radiation dermatitis in breast cancer patients [21]. The patient-reported Skindex-16 and STAT did not correlate with the physician-reported NIH CTC-AE scores.…”
Section: Discussionmentioning
confidence: 99%